2013
DOI: 10.1021/om3012568
|View full text |Cite
|
Sign up to set email alerts
|

Angular Distortions at Benzylic Carbons Due to Intramolecular Polarization-Induced Metal–Arene Interactions: A Case Study with Open-Shell Chromium(II) NHC Complexes

Abstract: The synthesis and full characterization of the unprecedented open-shell Cr(II) benzyl organometallic complexes [Cr(NHC)2(benzyl)2] (2) and [Cr(NHC*)(benzyl)2] (3) (NHC = N,N′-diisopropylimidazol-2-ylidene; NHC* = N,N′-bis(2,6-diisopropylphenyl)imidazol-2-ylidene) from [Cr(benzyl)3(THF)3] and [CrCl2(THF)2]/[Mg(benzyl)2], respectively, uncovered unusually acute angles (93° in 2 and 76° in 3) at the sp3 benzylic C of the coordinated benzyl ligands. Detailed theoretical analyses (DFT and CASPT2) of the four- and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 76 publications
1
6
0
Order By: Relevance
“…Single crystal X-ray diffraction demonstrated that 2 is a square planar complex (Figure ). The Cr–C bond distances in complex 2 range from 2.076(3) to 2.132(3) Å which is within the expected range (2.08–2.18 Å) given the limited number of Cr­(II) NHC complexes. The trans C1–Cr–C1′ and C2–Cr–C2′ angles are 170.54(14)° and 177.39(12)°, respectively, and the Cr atom sits on the calculated centroid of the plane of the NHC carbenes.…”
Section: Results and Discussionsupporting
confidence: 58%
“…Single crystal X-ray diffraction demonstrated that 2 is a square planar complex (Figure ). The Cr–C bond distances in complex 2 range from 2.076(3) to 2.132(3) Å which is within the expected range (2.08–2.18 Å) given the limited number of Cr­(II) NHC complexes. The trans C1–Cr–C1′ and C2–Cr–C2′ angles are 170.54(14)° and 177.39(12)°, respectively, and the Cr atom sits on the calculated centroid of the plane of the NHC carbenes.…”
Section: Results and Discussionsupporting
confidence: 58%
“…by reacting excess ligand with [CrCl 3 (thf) 3 ] or [Cr­(Me)­Cl 2 (thf) 3 ], led unexpectedly to the reduction of Cr III to Cr II and the isolation of 1 – 4 . Similar redox reactions between a Cr III complex and N , N ′-diisopropylimidazol-2-ylidene have been observed previously, but their mechanisms were not fully elucidated …”
Section: Resultsmentioning
confidence: 69%
“…The Cr–C benzyl bond distances in 5 and 6 (2.095(5)–2.149(1) Å) fall within the expected range , and are significantly shorter than the Cr–C NHC bonds (2.216(1) Å for 5 and 2.227(4) Å for 6 ). In both 5 and 6 , the three angles subtended at C benzylic show considerable differences: the C32–C31–Cr1 angle (107.20(8)° in 5 , 99.8(3)° in 6 ) is more acute than the other two (C39–C38–Cr1 121.57(8), 124.7(3)° and C25–C24–Cr1 117.07(9), 118.1(3)° in 5 and 6 , respectively).…”
Section: Resultsmentioning
confidence: 85%
“…The involvement of polarization induced interactions as contributing factor at the angular distortions at the benzylic C has been proposed recently. 16 Tantalum tribenzyl complexes with bulky monodentate aryloxides adopt trigonal bipyramidal geometry with equatorial benzyls, 17 and with bulky chelating bis aryloxides trigonal bipyramidal with two axial and one equatorial benzyls; 18 tridentate amine bis-phenolate ligands support octahedral geometry with meridional benzyls. 14 with Ta(CH2 t Bu3)3Cl2 in toluene giving, following work-up, a brown solid (2).…”
Section: Scheme 2 Complexes Described Hereinmentioning
confidence: 99%